Reindeer husbandry in Finland - Filppa, Jouni (Rangifer, 2005)
Reindeer are herded in the northernmost Finland over an area of 114 000 km2, about 35% of the area of the country. Herding is carried out both by Sami and Finns. The paper gives some statistics on the reindeer industry and underlines the importance of reindeer husbandry in Finland.